THE STUDY OFMOTIVATION TO BE SCIENCE TEACHER - Yuli Rahmawati (LPPM Universitas Negeri Jakarta, 2013)
This study aims is to examine several factors that influence people to choose the profession as a science teacher. The motivation is important factor that influence individual to have a good performance in their activities. Descriptive qualitative methodology through the semi-structured interview method is chosen to get the meaningful information of this study. The data was collected from four experienced science teachers who come from different countries which are Australia, America, Africa, and Philippines. The study found that several factors that motivated participants to be a teacher are family member, aspiration, role models, previous teaching experiences, teaching as powerful and manageable job, and educational background. However, all participants found interactions with their students have motivated them to be good and professional science teachers. Keywords: Motivation, science teacher, descriptive study